2009
DOI: 10.1007/s00018-009-0203-3
|View full text |Cite
|
Sign up to set email alerts
|

Sulfatase activities towards the regulation of cell metabolism and signaling in mammals

Abstract: In higher vertebrates, sulfatases belong to a conserved family of enzymes that are involved in the regulation of cell metabolism and in developmental cell signaling. They cleave the sulfate from sulfate esters contained in hormones, proteins, and complex macromolecules. A highly conserved cysteine in their active site is post-translationally converted into formylglycine by the formylglycine-generating enzyme encoded by SUMF1 (sulfatase modifying factor 1). This post-translational modification activates all sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 102 publications
(114 reference statements)
0
24
0
Order By: Relevance
“…2). In order to function, all sulfatases require posttranslational modification by sulfatase-modifying factor 1 (encoded by SUMF1) 21 , which regulates the sulfatase whose higher activities depend on greater amounts of sulfatase and SUMF1 transcripts 22 . We found that high expression of P. xylostella SUMF1 in third-instar larvae was coupled with significantly higher expression of the GSS1 and GSS2 genes relative to other members of the P. xylostella sulfatase gene family (Fig.…”
Section: (Supplementarymentioning
confidence: 99%
“…2). In order to function, all sulfatases require posttranslational modification by sulfatase-modifying factor 1 (encoded by SUMF1) 21 , which regulates the sulfatase whose higher activities depend on greater amounts of sulfatase and SUMF1 transcripts 22 . We found that high expression of P. xylostella SUMF1 in third-instar larvae was coupled with significantly higher expression of the GSS1 and GSS2 genes relative to other members of the P. xylostella sulfatase gene family (Fig.…”
Section: (Supplementarymentioning
confidence: 99%
“…Lysosomal desulfation of proteoglycans and other highly sulfated substrates is a prerequisite for their further degradation in the lysosomes 31 . A block in the lysosomal sulfatase activity, causing lysosomal accumulation of sulfated substrates will ultimately disrupt lysosomal function, which can be reflected by an impact on the enzymatic function of other lysosomal enzymes.…”
mentioning
confidence: 99%
“…The importance of lysosomal sulfatases in human metabolism is underlined by the study of inherited diseases resulting from defects in sulfatase function 31 . Since SUMF1 is an essential activator of all cellular sulfatases, mutations in this gene cause the most severe disease variant, MSD, in which all sulfatase activity is severely reduced 12,32 .…”
mentioning
confidence: 99%
“…Extracellular sulfatases (Sulfs) are hydrolytic enzymes that regulate cell metabolism and signaling [1]. There are 17 distinct sulfatases in humans and 14 sulfatases in rodents.…”
Section: Introductionmentioning
confidence: 99%
“…There are 17 distinct sulfatases in humans and 14 sulfatases in rodents. Sulfatases are classified as lysosomal, nonlysosomal, and Sulfs, according to their localization [1,2]. Sulfs are designated as heparin sulfate 6-O-endosulfatases, and to date, human, mouse, and rat orthologs have been cloned [3,4].…”
Section: Introductionmentioning
confidence: 99%